TINJAUAN KONDISI FISIK ATLET WUSHU KABUPATEN KERINCI - Edwarsyah Edwarsyah; Istighfar Oradia Linas (Jurnal Muara Olahraga, 2018)
The problem in this study was the athletes’s failureinthe game due to tiredness, even though the game time has not run out. Furthermore, in competing, Wushu athletes often lose speed in attacking or defending, the body was less agile to dodge and even punches, kicks and kickbacks were less powerful and not so hard.The type of the research was descriptive research. The population were all Wushu Athletes in Kerinci Regency in 2018. 15 samples were chosen. The sampling technique was done through "total sampling". The data consisted of primary and secondary data. The technique of data analysis was descriptive statistical analysis.The results shown that: 1) The level of limb muscle explosive power wushu athletes in Kerinci Regency was in the category of Prima and good, 2) The level of agility possessed by the Wushu athletesin Regency Kerinci was in the good category. It could be proved by the score. 7 out of 15 athletes scored were <15.5 which categorized in the excellent category, 3) Level of speed of Wushu athletes in Kerinci Regency were in good category, this was indicated by the acquisition of a value between 6.44-7.31 that owned by 8 athletes with a percentage of 53.33 %. These were classified as a good classification.